Cardiogenic shock and hyperlactatemia in a patient with Shoshin Beriberi in a general hospital in Lima, Peru. A case report - Zegarra Piérola, Jaime Wilfredo (2024)
Introduction: Shoshin Beriberi is a disease generated by thiamine deficiency and is characterized by acute fulminant cardiac dysfunction (1). Objective: To highlight cardiogenic shock and hyperlactacidemia in a patient with shoshin beriberi in an intensive care unit of a general hospital. Material and method: The information was taken from the electronic medical history of the intensive care unit (ICU) of the Cayetano Heredia National Hospital (HNCH) and from laboratory and image records. Case: 22-year-old female patient, with a history of anorexia nervosa, multisystem tuberculosis (TBC); with abdominal pain, vomiting, oral intolerance, prolonged fasting, received total parenteral nutrition (TPN) without thiamine intake and with hospitalization for 40 days on the general floor; Admission to the ICU in cardiogenic shock and hyperlactacidemia with serum lactate 13.8 mmol/L. With sepsis ruled out, an acute vascular event and cardiogenic shock refractory to the use of norepinephrine, vasopressin and dobutamine, the diagnosis of shoshin beriberi was considered and 300 mg of intravenous thiamine was administered, with a rapid response, achieving hemodynamic and cardiopulmonary stabilization, with subsequent discharge from ICU and hospital. Conclusion: Cardiogenic shock and hyperlactacidemia were manifestations of shoshin beriberi, with sepsis and acute vascular event ruled out and with the use of thiamine hemodynamic and cardiopulmonary stabilization was achieved. Keywords: cardiogenic shock, hyperlactacidemia, shoshin beriberi, thiamine